Tahlili hadis - Radhie Munadi (Fakultas Ushuluddin dan Filsafat Universitas Islam Negeri Alauddin Makassar, 2022)
In everyday life, the term bribery is no stranger to hearing. Day after day bribery cases are often found in several media. However, it is often found that only the briber is at fault. Whereas in the explanation of muhaddistin scholars, there are 4 elements in bribery, namely the briber, the recipient of the bribe, the intermediary of the bribe and the treasure of the bribe. Explanations related to some of these elements are obtained by several approaches, one of which is tahlili hadith. Bribery in a hadith perspective with a tahlili approach is needed so that the understanding of the bribery hadith is more detailed and clear. In fact, all these elements are cursed and kept away from goodness. This study tries to provide a new scientific treasure in the content of hadith to understand bribery with the tahlili hadith approach. Keywords: Hadith, Bribery, Tahlili